Building the Welfare of East Java Migrant Workers Through the Maqashid Syariah Approach in Economic and Social Empowerment - Hariyanto, Wahid; Masykuroh, Ely; Wibawanto, Alwan; Supriati, Eny; Kolis, Nur (MUSLIM HERITAGE, 2025)
East Java with 41.8 million people is the province that sends the highest number of migrant workers, especially from Malang, Bojonegoro, Lamongan, Kediri, and Ponorogo. Although female migrant workers contribute IDR 251.1 trillion in remittances (2024), they still face various social and spiritual problems. This study aims to analyze the welfare of female migrant workers from the perspective of Maqashid Syariah by reviewing the fulfillment of the five main dimensions of Hifdz ad-Din, Hifdz an-Nafs, Hifdz al-'Aql, Hifdz an-Nasab, and Hifdz al-Maal. Using a qualitative descriptive method with a comparative approach to understand the dynamics of the welfare of female migrant workers in four purposively selected districts, namely Ponorogo, Kediri, and Malang. Data were collected through in-depth interviews (including video calls for overseas informants), participatory observation, and documentation analysis. Data sources include migrant and ex-migrant workers, employees of the Manpower Office, lecturers, university LPPM teams, and written documents as secondary data. Data analysis uses the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and conclusion drawing and verification at two levels of single case analysis and cross-case analysis. The results of the study show that the welfare of female migrant workers is only fulfilled in two aspects, namely Hifdz al-Maal (maintenance of property) and Hifdz al-'Aql (maintenance of reason). The other three aspects of Hifdz an-Nafs, Hifdz an-Nasab, and Hifdz ad-Din have not been fulfilled optimally and require serious attention through policies that are gender justice and based on maqashid values. The novelty of this research lies in the comprehensive analysis of the portrait of the welfare of female migrant workers using the concept of Maqashid Syariah Ash-Syatibi, which not only emphasizes economic aspects, but also the dimensions of education, family, security, and religious compliance. Abstrak Jawa Timur dengan 41,8 juta penduduk menjadi provinsi pengirim pekerja migran tertinggi, terutama dari Malang, Bojonegoro, Lamongan, Kediri, dan Ponorogo. Meski PMI perempuan menyumbang remitansi Rp251,1 triliun (2024), mereka masih menghadapi berbagai persoalan sosial dan spiritual. Penelitian ini bertujuan untuk menganalisis kesejahteraan pekerja migran perempuan dari perspektif Maqashid Syariah dengan meninjau keterpenuhan lima dimensi utama Hifdz ad-Din, Hifdz an-Nafs, Hifdz al-‘Aql, Hifdz an-Nasab, dan Hifdz al-Maal. Menggunakan metode deskriptif kualitatif dengan pendekatan komparatif untuk memahami dinamika kesejahteraan pekerja migran perempuan di empat kabupaten yang dipilih secara purposif, yaitu Ponorogo, Kediri, dan Malang. Data dikumpulkan melalui wawancara mendalam (termasuk panggilan video bagi informan di luar negeri), observasi partisipatif, dan analisis dokumentasi. Sumber data mencakup pekerja migran dan eks migran, pegawai Dinas Tenaga Kerja, dosen, tim LPPM perguruan tinggi, serta dokumen tertulis sebagai data sekunder. Analisis data menggunakan model interaktif Miles, Huberman, dan Saldana yang meliputi kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan pada dua tingkat analisis kasus tunggal dan lintas kasus. Hasil penelitian menunjukkan bahwa kesejahteraan pekerja migran perempuan baru terpenuhi pada dua aspek, yaitu Hifdz al-Maal (pemeliharaan harta) dan Hifdz al-‘Aql (pemeliharaan akal). Adapun tiga aspek lainnya Hifdz an-Nafs, Hifdz an-Nasab, dan Hifdz ad-Din belum terpenuhi secara optimal dan memerlukan perhatian serius melalui kebijakan yang berkeadilan gender dan berbasis nilai maqashid. Kebaruan penelitian ini terletak pada analisis komprehensif potret kesejahteraan pekerja migran perempuan dengan menggunakan konsep Maqashid Syariah Asy-Syatibi, yang tidak hanya menekankan aspek ekonomi, tetapi juga dimensi pendidikan, keluarga, keamanan, dan kepatuhan beragama.